2010
DOI: 10.1186/1471-2407-10-434
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of hnRNP A/B proteins in human non-small cell lung cancer: parallel assessment of protein and mRNA levels in paired tumour/non-tumour tissues

Abstract: BackgroundHeterogeneous nuclear ribonucleoproteins (hnRNPs) of the A/B type (hnRNP A1, A2/B1, A3) are highly related multifunctional proteins participating in alternative splicing by antagonising other splicing factors, notably ASF/SF2. The altered expression pattern of hnRNP A2/B1 and/or splicing variant B1 alone in human lung cancer and their potential to serve as molecular markers for early diagnosis remain issues of intense investigation. The main objective of the present study was to use paired tumour/non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 31 publications
(60 reference statements)
2
43
0
Order By: Relevance
“…Furthermore, previous studies from our laboratory and others demonstrated functional oncogenic roles for several splicing factors, including hnRNP A2/B1 (Karni et al 2007;Golan-Gerstl et al 2011;Lefave et al 2011;Cohen-Eliav et al 2013). Overexpression of hnRNP A1/A2 proteins has been reported in several cancers (Zhou et al 2001a(Zhou et al , 2013Ushigome et al 2005;Li et al 2009;Ma et al 2009;Boukakis et al 2010;Wang et al 2011). In HCC, the splicing factor SRSF1 has been shown to regulate splicing of tumor suppressors such as KLF-6 (Munoz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies from our laboratory and others demonstrated functional oncogenic roles for several splicing factors, including hnRNP A2/B1 (Karni et al 2007;Golan-Gerstl et al 2011;Lefave et al 2011;Cohen-Eliav et al 2013). Overexpression of hnRNP A1/A2 proteins has been reported in several cancers (Zhou et al 2001a(Zhou et al , 2013Ushigome et al 2005;Li et al 2009;Ma et al 2009;Boukakis et al 2010;Wang et al 2011). In HCC, the splicing factor SRSF1 has been shown to regulate splicing of tumor suppressors such as KLF-6 (Munoz et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…hnRNP A1 hnRNP A1 has been found to be deregulated in various types of cancers, including colon, 89 lung, 90 and liver, 91 usually leading to overexpression of hnRNP A1 mRNA and protein. Expression levels are correlated with increased proliferation 92,93 and tumor metabolism.…”
Section: The Oncogenic Activities Of Hnrnp Splicing Factorsmentioning
confidence: 99%
“…27 Numerous of researches indicate that HNRNPA2B1was involved in the tumorigenesis of pancreatic cancer, 28,29 prostate cancer, 30 hepatocellular carcinoma, 31 and LC. 32 Higher expression level of HNRNPA2B1 in tissues from patients with gastric adenocarcinoma, 33 non-small cell LC 34 and hepatocellular carcinoma 35 has been reported. The autoimmune responses to HNRNPA2B1 have been described previously in patients with hepatitis, 36 but not reported for cancer.…”
Section: Discussionmentioning
confidence: 98%